Real-Time Auralisation of Outdoor Sound Propagation - Stienen, Jonas (Aachener Beiträge zur Akustik, 2023)
Auralisation describes the process of generating and presenting audible sound using computer programs and audio hardware. Since the result is perceived naturally by the human's auditory system, a demonstration by means of auralisation is easily comprehensible and neither requires background knowledge nor expertise. Producing auralisation under real-time constraints increases the implementation demands significantly. Real-time auralisation is required in applications that respond to user interaction, for example, in interactive Virtual Reality (VR) environments. The realisation of a real-time auralisation application for outdoor environments represents a promising addition to current noise assessment procedures. It also delivers the foundation for the auditory modality in outdoor VR scenarios, which can serve as as an audio-video tool for perception-related scientific investigations. Traditional approaches often neglect the time-variant characteristic of dynamically moving sound sources and receivers, treating an acoustic environment as temporarily static on a frame-by-frame basis. Adaption to dynamic events is implemented by transition of sequences of time-invariant simulations, which is contradictory to the highly dynamic nature of outdoor scenarios. This book describes a system that attaches increased importance to fast geometric diffraction simulations and employs an audio rendering network that reflects the time-variant nature of dynamic outdoor sound propagation.